Budget reform in OECD member countries Common trends - Blöndal, Jón R.. (OECD Publishing, 2003)
From the early 1990s, the fiscal position of OECD member countries improved steadily each year, from a deficit of 5% of GDP for member countries as whole in 1993 to a perfect balance in the year 2000, i.e. neither a deficit nor a surplus. In 2001, member countries experienced a deficit of 1% of GDP. Table 1 depicts the general government financial balances of selected OECD member countries. This goes to show the historical pattern in member countries: achieving fiscal consolidation is a slow process and successes in fiscal consolidation can quickly dissipate. A very short time ago, several OECD member countries believed that they were on a long-term track for fiscal surpluses; the era of deficits had been overcome. This did not turn out to be the case; surpluses turned out to be a very short-lived phenomenon for many countries